Inner Conflict of the Main Character in the Narasi 2021 Novel by Tenderlova - Eka Ardini, Fitri; Kanzunnudin, Mohammad; Roysa, Mila (Saba Jaya Publisher, 2024)
This study aims to describe the inner conflict experienced by the main character in the novel Narasi 2021 by Tenderlova. Using the literary psychology approach of Sigmund Freud's emotion classification theory. This study uses qualitative descriptive research with data collected in the form of words, sentences and dialogue excerpts, not numbers. Data collection in this study was obtained from quotes of words, sentences and dialogues contained in the novel Narasi 2021 by Tenderlova. The data source was obtained from the novel Narasi 2021 in this study. The data collection technique used is the reading and note-taking technique. The reading and note-taking technique is carried out by reading and taking notes to obtain data from data sources. Data analysis techniques include data reduction, data presentation and drawing conclusions. The results of the study show the classification of emotions experienced by the main character in the novel Narasi 2021 by Tenderlova. Including guilt, sadness, hatred, shame, love, and loss.